Atorvastatin and insulin equally mitigate brain pathology in diabetic rats - Wasana Pratchayasakul (2018)
© 2018 Elsevier Inc. Although insulin and atorvastatin have been shown to exert glycemic control and could improve brain function, the effects of atorvastatin or insulin as well as the combination of atorvastatin plus insulin on brain pathology in diabetes mellitus type 1 (T1DM) are unclear. Therefore, this study investigated the effect of atorvastatin, insulin or combined drugs on brain pathology in streptozotocin-induced diabetic rats. Thirty-six male rats were divided into two groups, a control group (n = 12) and a diabetic or experimental group (n = 24). Diabetic rats were further divided into four groups (n = 6/group) and the groups received either a vehicle (normal saline), atorvastatin (10 mg/kg/day), insulin (4 U/day) or a combination of the drugs for 4 weeks. The control group rats were divided into two groups (n = 6/group) to receive either just the vehicle or atorvastatin for 4 weeks. We found that streptozotocin-induced diabetic rats developed hyperglycemia, showing evidence of increased brain oxidative stress, impaired brain mitochondrial function, increased brain apoptosis, increased tau protein expression, increased phosphorylation of tau protein expression and amyloid beta levels, and decreased dendritic spine density. Although atorvastatin and insulin therapies led to an equal reduction in plasma glucose level in these diabetic rats, the combined drug therapy showed the greatest efficacy in decreasing plasma glucose level. Interestingly, atorvastatin, insulin and the combined drugs equally mitigated brain pathology. Our findings indicate that the combined drug therapy showed the greatest efficacy in improving metabolic parameters. However, atorvastatin, insulin and the combined drug therapy shared a similar efficacy in preventing brain damage in T1DM rats.